PERANCANGAN APLIKASI MANAJEMEN PERALATAN JARINGAN KOMPUTER - Sudirman Sudirman; Sumarsono Sumarsono; Anton Setiawan Honggowibowo (Compiler, 2013)
Nowadays computer not only as a device, but also it needs to data access in order to more efficient and to do tasks that involve the other computers, so network administrator needs some ease and efficiency when configure and network troubleshoot. Therefore, with router a protocol can be share to the other network devices, beside that switch can also filters and flows the packet that exist in a LAN (Local Area Network), so it can work for anything protocol packet. This network equipment management application is to configure utility with input several data that available so that more efficient for user. The result o f this application is can help administrator and newborn administrator to ease in configure router.